Transfusion Management of Incident Dialysis Patients in Canada: A Prospective Observational Study. Issue 1 (5th June 2018) - Bello, Aminu K.; Ribic, Christine M.; Cournoyer, Serge H.; Kiaii, Mercedeh; LeBlanc, Martine; Poulin-Costello, Melanie; Churchill, David N.; Muirhead, Norman
Background: Several studies have demonstrated harm associated with using erythropoiesis-stimulating agents (ESA) to achieve higher hemoglobin (Hb) levels. Subsequently, more conservative use of ESAs has changed anemia therapy in patients with chronic renal failure. Objective: The objectives were to identify transfusion rates in hemodialysis (HD) patients during the first year of therapy, to identify factors associated with the probability of transfusion, describe reasons for the transfusions, and identify the Hb values associated with each transfusion. An exploratory objective was to describe the age of red blood cell transfusions. Design: This was a multicenter prospective observational cohort study. Setting: There were 12 study sites in 5 Canadian provinces. The study was performed from 2012 to 2014. Methods: The study patients were adult incident chronic HD patients in these centers. Patients with acute kidney injury, peritoneal dialysis, and planned transfer to satellite units were excluded. Patients had to receive at least 1 month of chronic HD to be eligible. Data for 3 months prior to HD were obtained by retrospective chart review. Prospectively, charts were reviewed monthly for 12 months for data abstraction. Results: There were 314 patients enrolled and 79.9% completed 12 month follow-up. Ninety-four (29.9%) patients received at least 1 unit of blood. During the first 90 days, the transfusion episode rate was 148.4 per 100 patient-years compared with 62.6 per 100 patient-years post 90 days. The most frequent indication was a low Hb value (92%) with gastrointestinal bleeding, surgical blood loss, and fatigue accounting for 9.9%, 8.6%, and 4.5%, respectively. Some patients had >1 indication. The mean Hb values prior to transfusion episodes ranged from 75.3 to 78.6 g/L. Cox regression analysis on time to first transfusion and time to first hospitalization/death both showed an association with inpatient initiation of HD. Some 37.5% initiated HD as an inpatient and differed from those starting as an outpatient. They had less predialysis care and laboratory data suggested more inflammation. The mean and median ages of the blood units transfused were 24.9 (SD = 10.0) and 23 days (interquartile range = 17-33). Conclusions: This work reported the blood transfusion rate in incident HD patients in Canada during a period associated with conservative ESA prescription. The major indication for transfusion was a low Hb rather than clinical symptoms. Initiation of HD as an inpatient was independently associated with the probability of receiving a blood transfusion. These findings require further investigation.